2010
DOI: 10.12968/bjom.2010.18.3.46917
|View full text |Cite
|
Sign up to set email alerts
|

Rising rates of intervention in childbirth

Abstract: This article presents the findings of research which investigated what is shaping the understanding of the public and also the practice of health professionals in relation to rising rates of intervention in childbirth. This research was carried out in response to the increasing rates of intervention in childbirth in Aotearoa, New Zealand using critical hermeneutics methodology. The particular approach used was critical interpretation as formulated by Hans Kogler. The findings revealed that the everyday world a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Close to 70% of college students from Quebec supported this view when they agreed that it is a woman’s right to choose a CS for herself even if there is no medical reason for it (Saroli-Palumbo, Hsu, Tomkinson, & Klein, 2012). This was also a major theme in McAra Couper et al’s study (2010). These findings suggest that the next generation of childbearing women is interpreting birth from a women’s rights perspective, and value autonomy when making decisions about labor and birth.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Close to 70% of college students from Quebec supported this view when they agreed that it is a woman’s right to choose a CS for herself even if there is no medical reason for it (Saroli-Palumbo, Hsu, Tomkinson, & Klein, 2012). This was also a major theme in McAra Couper et al’s study (2010). These findings suggest that the next generation of childbearing women is interpreting birth from a women’s rights perspective, and value autonomy when making decisions about labor and birth.…”
Section: Discussionmentioning
confidence: 71%
“…Young women in both the high and low fear groups expressed concerns about the pain of childbirth. McAra Couper, Jones, and Smythe (2010) found a similar focus on pain when interviewing maternity care providers and the public about what shaped their understanding of interventions in childbirth. They concluded that individuals constructed pain as something to be avoided and linked avoidance of pain to valuing technology and control in childbirth.…”
Section: Discussionmentioning
confidence: 95%
“…Women most commonly fear labour pain and harm to the baby (Geissbuehler andEberhard, 2002, Melender, 2002;Saisto and Halmesmaki, 2003;Maier, 2010;McAra Couper et al, 2010); they view their fears as mitigated by obstetric interventions, such as epidural anaesthesia for relief of labour pain and planned CS to avoid labour pain (Stoll & Hall, in press-a). Most studies of childbirth fear have focused on pregnant women and their partners, with little attention paid to fear of birth and preferences for obstetric interventions among the next generation of maternity care consumers (Saroli-Palumbo et al, 2012;Stoll and Hall, in press-a, in press-b).…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Vital Statistic Reports the repeat cesarean delivery rate was nearly 90% in 2003 (Menacker, 2005). Today surgical delivery is viewed by many health care professionals and consumers as a desirable option (Hewer, Boschma, & Hall, 2009;McAra-Couper, Jones, & Smythe, 2010).…”
Section: Background and Significancementioning
confidence: 99%